Influence of Preload on Failure Modes of Hybrid Metal-Composite Protruding Bolted Joints - Calin-Dumitru COMAN (INCAS Bulletin, 2021)
This paper presents the effects of torque preload on the damage initiation and growth in the CFRP (Carbon Fiber Reinforced Polymer) composite laminated adherent of the single-lap, single-bolt, hybrid metal-composite joints. A detailed 3D finite element model incorporating geometric, material and friction-based contact full nonlinearities is developed to numerically investigate the preload effects on the progressive damage analysis (PDA) of the orthotropic material model. The PDA material model integrates the nonlinear shear response, Hashin-tape failure criteria and strain-based continuum elastic properties degradation laws being developed using the UMAT user subroutine in Nastran commercial software. In order to validate the preload effects on the failure modes of the joints with hexagonal head bolts, experiments were conducted using the SHM (Structural Health Monitoring) technique. The results showed that the adherent torque level is an important parameter in the design process of an adequate bolted joint and its effects on damage initiation and failure modes were quite accurately predicted by the PDA material model, which proved to be computational efficient and can predict failure propagation and damage mechanism in hybrid metal-composite bolted joints.